Effectiveness of battery electric vehicle promotion on particulate matter emissions reduction. (April 2021) - Choi, Hyunhong; Koo, Yoonmo
Graphical abstract: Highlights: Investigated environmental impact of battery electric vehicle promotion policy. Battery electric vehicle promotion alone not very effective at reducing pollutants. Battery electric and diesel vehicles have weak substitutional relationship. Direct regulation of diesel vehicles has substantial impact on reducing pollutants. Targeted rebate to promote transition from diesel to electric can be considered. Abstract: Quantifying environmental benefits from battery electric vehicles (BEVs) requires an understanding of the long-term substitutional relationships among different vehicle technologies. This study analyzes how BEV promotion can contribute to reductions in particulate matter (PM) emissions in Korea and investigates effective long-term policy options. Using a choice model, this study simulates consumers' vehicle replacement behavior under various policy scenarios from 2018 to 2025. The results show that BEV promotion alone has limited effectiveness at reducing PM emissions because BEV purchases were predominantly made by gasoline vehicle owners while diesel vehicles are the key source of emissions. This finding is significant because investment in BEV promotion in Korea specifies PM emissions reductions as their core objective and legal basis. Investigation of additional policy options suggests that the combination of direct regulations on diesel vehicles and a targeted rebate to promote substitution between diesel vehicles and BEVs can reduce PM emissions by ~13%.